“Efektivitas Mekanisme REDD (Reducing Emissions from Deforestation and Forest Degradation) sebagai Kebijakan yang Dihasilkan oleh Rezim Perubahan Iklim UNFCCC - Debby Rizqie (Department of International Relations, Universitas Andalas)
The discussion of climate change has entered the international political stage since the 1980s, and as an international response, UNFCCC was founded as a forum to handle this issue. UNFCCC has produced the Kyoto Protocol – an agreement which obligates nations to halt the rapid effect of global warming. Through the course of its life, the Protocol has been regarded as incompetent in achieving the goals uttered in the convention. Further discussion was needed, and the later forums finally decide to improve the protocol by establishing REDD, a proposal which focuses specifically on green house gas emissions from forestry. To this present moment, REDD has remained a non-binding and unofficial agreement, but REDD has been applied in many states, therefore its effectivity remains a question worth asking. By using a mixed method approach, and studying documents to achieve adequate amount of data, this research attempts to answer the questions regarding the effectivity of the REDD mechanism. The international regime theory approach will be used, which focuses on the theory of regime effectiveness, implementation concept and compliance. This research concludes that REDD falls under the category